Lipid composition of normal male rat islets - Díaz, Graciela (1988)
Lipid composition was studied in fresh isolated isolets from normal male rats. Extractable lipids represent 1856 μg per mg islet protein. In such extracts, phospholipids and neutral lipids reprsent 13.5% and 86.5%, respectively. Phosphatidylcholine (45.8%) and phosphatidyl-ethanolamine (20.6%) were the major components of the phospholipid fraction, and phosphatidylinositol (8.9%) was the minor component. Esterified cholesterol (38.5%), cholesterol (25.5%) and free fatty acids (24.4%) were the major components of the neutral lipid fraction. Fatty major components of the neutral lipid fraction. Fatty acids esterified to phospholipids account for 619.7 pmol/islet, and, 2710 pmol/islet were esterified to neutral lipids. In the phospholipid fraction, saturated and unsaturated fatty acids were in a similar proportion. Conversely, in the neutral lipids, two-thirds of the fatty acids were unsaturated. The ω6 family was the main component of the phospholipid unsaturated fatty acids. In the ω6 and ω3 families, the long-chain fatty acids represent the main components. In the neutral lipid fraction, a different percentage of each family was found: ω3>ω6>ω9. The long-chain polyunsaturated fatty acids were also predominant species in the ω6 and ω3 families. Further studies on the lipid composition of islets, obtained from rats with normal and altered islet functions, could provide new insights into the knowledge of the mechanism of insulin secretion.